2009
DOI: 10.1211/jpp/61.08.0014
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity and possible mechanism of extract from <I>Mikania laevigata</I> in carrageenan-induced peritonitis

Abstract: In conclusion the anti-inflammatory effect induced by guaco extract may be by inhibition of pro-inflammatory cytokine production at the inflammatory site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 23 publications
(28 reference statements)
0
29
0
Order By: Relevance
“…Though many workers (Alves et al, 2009;Maldini et al, 2009) have shown inhibition of PBMC proliferation by lupeol acetate, this is the first report where in we have shown that at very low concentration (0.5 g/ml) (2S)-5,7,4 -trihydroxy flavanone 4 -O-␤-d-glucoside inhibited PBMC proliferation. As evidenced by MTT assay less than 20% cytotoxicity was observed in PBMCs treated with Compound 1 (8 g/ml) and Compound 2 (0.5 g/ml) at their respective IC 50 values.…”
Section: Discussionmentioning
confidence: 46%
“…Though many workers (Alves et al, 2009;Maldini et al, 2009) have shown inhibition of PBMC proliferation by lupeol acetate, this is the first report where in we have shown that at very low concentration (0.5 g/ml) (2S)-5,7,4 -trihydroxy flavanone 4 -O-␤-d-glucoside inhibited PBMC proliferation. As evidenced by MTT assay less than 20% cytotoxicity was observed in PBMCs treated with Compound 1 (8 g/ml) and Compound 2 (0.5 g/ml) at their respective IC 50 values.…”
Section: Discussionmentioning
confidence: 46%
“…Alves et al 37 ., showed that the hydroalcoholic extract of M. laevigata reduces the migration of neutrophils into the peritoneal cavity by a mechanism dependent on pro-inflammatory cytokines (TNF-α and IL-1β).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, there was no change in urea levels, indicating the absence of alterations in the kidney. Additionally, the LD 50 was found to be almost 75-fold higher than the pharmacological dose tested (Alves et al, 2009). The potential genotoxicity of the dichloromethane fraction of the hydroalcoholic extract was evaluated on plasmid DNA using an alkaline lysis procedure, in which plasmid DNA was treated with SnCl 2 and the M. glomerata extract fraction.…”
Section: Toxicological Studiesmentioning
confidence: 91%
“…Hydroalcoholic extracts are the most common preparations that have been commercialized for therapeutic purposes, and the majority of phytochemical assays that have been conducted have been to evaluate their chemical compositions. Thus, using different analytical procedures, the presence of a large number of compounds has been described, including stigmasterol, phytol, 1-ethoxy-1-phenylethanol, 4-hydroxy-3,5-dimethoxybenzaldehyde, hexanoic acid, ethyl hexadecanoate, ethyl linoleoate, kaurenol, an isomer of kaurenoic acid, spathulenol, hexadecanoic acid, 9,12,15-octadecatrienoic acid, cupressenic acid, isopropiloxigrandifloric acid, 2-5-ciclohexadiene-1,4-dione,2,6-bis, 1-octadecene, octadecanoic acid, ester diterpenic, caryophyllene oxide, 10, 13-octadecadienoic acid, isobutiloxigrandifloric acid, trans-cariofileno, 8,11-octadecadienoic acid, lupeol, lupeol www.intechopen.com Toxicity and Drug Testing 300 acetate, benzoylgrandifloric and cinnamoylgrandifloric acids (Oliveira et al, 1993;Moura et al, 2002;Biavatti et al, 2004;Santos, 2005;Yatsuda et al, 2005;Bertolucci et al, 2008;Alves et al, 2009;Bolina et al, 2009;Muceneeki et al, 2009). In quantitative terms, the most prevalent metabolites of hydroalcoholic extracts are coumarin (1,2-benzopyrone) (Biavatti et al, 2004;Bueno & Bastos, 2009), o-coumaric acid (Santos, 2005), dihydrocoumarin (Alves et al, 2009), syringaldehyde (Muceneeki et al, 2009) and kaurenoic acid (Vilegas et al, 1997a;Vilegas et al, 1997b;Yatsuda et al, 2005;Bertolucci et al, 2008).…”
Section: Chemical Constituentsmentioning
confidence: 99%
See 1 more Smart Citation